Preferensi Pelaku Usaha Mikro Kecil Menengah terhadap Alternatif Pembiayaan Syariah di Perbankan Syariah - Sharoh, Siti Mayyas; Nur Aini, Aprilia Faizah; Kholmi, Masiyah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This research examines the preferences of Micro, Small and Medium Enterprises (MSMEs) actors towards Sharia financing schemes offered by Islamic banking. The research uses a qualitative approach with a descriptive-analytical method based on a literature study of various relevant scientific literature, articles, books, and reports. The focus of the research is to understand the factors that influence the tendency of MSMEs to choose certain schemes, as well as their relationship with the understanding of Islamic economic principles, especially usury. Usury, which is expressly forbidden in Islam, involves unfair profits from loans that cause significant financial burdens, especially for small businesses. The high interest rates imposed by conventional financial institutions often result in increased debt, decreased productivity and even bankruptcy for MSMEs. The research findings show that MSMEs' preference for Islamic financing is influenced by the level of understanding, trust in sharia principles, ease of procedures, and risk perception. The Islamic financial system offers an alternative that complies with sharia principles and provides a more equitable and mutually beneficial financing solution.